(untitled) (Research, Society and Development, 2022)
Introduction: Chronic Diseases represent the greatest burden of morbidity and mortality in Brazil. Polypharmacy can be classified as quantitative and qualitative. Among the concepts for the quantitative is the use of two or more drugs. In turn, qualitative polypharmacy considers the rationalization of pharmacological therapy. Objective: Based on these concepts, the objective of this work is to analyze the consequence of polypharmacy in patients with chronic diseases, with emphasis on adverse reactions and drug interactions and to show the importance of the pharmacist in order to reduce this consumption practice. Methodology: the research was developed through searches on the Scielo (Electronic Library Scientifc Electronic Library Online) and Google academic platforms. Based on a literature review, according to Silva, (2019), which is responsible for aligning an overview of the in-depth literature on the selected topic. The following descriptors were used: “Polypharmacy; “Pharmaceutical Care”, “Patient safety”. Finally, 23 publications were selected to compose the study. Conclusion: Polypharmacy is a common practice among the population and may be related to the exacerbated or inappropriate use of medications. Drug review and prescription potential should be evaluated, especially by general practitioners or pharmacists, in order to personalize treatment for people with multimorbidity or specific vulnerability. In addition, monitoring for the potential occurrence of drug interactions is important.